Smart cities and innovations: Addressing user acceptance with virtual reality and Digital Twin City. Issue 4 (28th September 2022) - Michalik, David; Kohl, Per; Kummert, Anton
Abstract: The transformation into smart cities is imminent to meet the rising number of urban problems and challenges. Digital technologies offer great potential to develop smart solutions, especially in the areas of public administration, energy, infrastructure and mobility. For the successful diffusion, the acceptance of the individual is a crucial part, which can be addressed by an immersive experience along with the personal collection of insights of the innovation. However, at the same time a paradox arises as many new developments are still in the making and therefore, are not yet available to the public. Immersive virtualisation technologies such as Virtual Reality (VR) offer great potential to solve this problem. In this study, the usability of VR technology to address individual's innovation barriers in general and to explore the use of emerging digital twin cities (DTC) is analysed, as they provide an ideal basis for the customised creation of immersive VR‐applications. Although several themes and applications regarding the potential of DTCs have been addressed in literature, their explicit use in the field of acceptance research has not been pursued. Therefore, a new methodology is introduced and first implementations and results are presented and discussed.